Profit or not: Education on picking the mutual fund - Vita Elisa Fitriana; Supeni Anggraeni Mapuasari (Universitas Muhammadiyah Magelang, 2022)
Low financial literacy causes finances to be managed not optimally, including household finances. On the other hand, women have a strategic role in the family, so that women's financial empowerment can have implications for the level of welfare. Various financial objectives can be achieved through selecting the right investment instruments, in accordance with the length of the investment and risk preferences. With proper analysis, mutual funds can be an investment option that offers various types of risk and return to manage finances. This article aims to summarize community service materials related to procedures for purchasing and selecting mutual funds so that people are wiser and more appropriate in investing.